1961
DOI: 10.1017/s0007485300055462
|View full text |Cite
|
Sign up to set email alerts
|

The population dynamics ofCryptolestes ferrugineus(Stephens) (Col., Cucujidae) in flour and on Manitoba wheat

Abstract: Davies (1949) found that whereas cultures of adults of Cryptolestes pusillus (Schonh.) had a high fecundity on flour or crushed wheat, on sound wheat the production of larvae was negligible and the adult mortality very high. Even when slightly damaged wheat was used, few larvae survived into the later instars. Williams (1954) confirmed that newly hatched larvae are unable to enter unblemished grains, and Bilett (1949) found this was also true for larvae of Cryptolestes ferrugineus (Steph.).Nevertheless, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1961
1961
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…SMITI.~ (1959) calculated the intrinsic rate of increase of C.ferrugineus as 0. 90 per week, or 40 times a month at 30~ The speed of its development increases with increasing temperature (AshBY 1961). The phenomenal increase in its population from February 22 to March 21 in the fully-developed hot spot (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…SMITI.~ (1959) calculated the intrinsic rate of increase of C.ferrugineus as 0. 90 per week, or 40 times a month at 30~ The speed of its development increases with increasing temperature (AshBY 1961). The phenomenal increase in its population from February 22 to March 21 in the fully-developed hot spot (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…A number of species of grain beetles are casually cannibalistic, like the Anura, and this appears to be an important mortality factor in certain circumstances (Crombie, 1944;Boyce, 1946). In the case of the grain beetle Cryptolestes ferrugineus, cannibalism and competition by a large cohort of larvae or adults has been reported to prevent recruitment of further individuals to the population from eggs in certain circumstances (Ashby, 1961). Alm (1946Alm ( , 1951 similarly suggested that the almost complete dominance over a period of several years of a single year class of perch (Percafluviatilis) in small dystrophic lakes he studied, was due to its predation on the broods of subsequent years.…”
Section: Mortality and Population Densitymentioning
confidence: 99%
“…E.H., eggs were allowed to hatch, the first-instar larvae being removed. No damaged eggs or other signs of cannibalism were seen at any time (see also Ashby, 1961). A considerable proportion of the eggs was laid through the muslin on to the cork where, given the opportunity, larvae readily developed in the lenticular material.…”
mentioning
confidence: 92%